The ageing patient with haemophilia. (February 2015) - Canaro, Mariana; Goranova‐Marinova, Veselina; Berntorp, Erik
Abstract: Older patients with haemophilia (PWH) face many challenges related not only to haemophilia but also to general comorbidities associated with ageing. This article discusses the clinical experience published about the high prevalence of diseases in older PWH. These conditions are managed in the general population by healthcare workers with little training in haemophilia. Haemophilic arthropathy is common in elderly PWH. Prophylaxis starting at an early age in sufficient dose regimens to prevent arthropathy did not occur in patients who are now older than around 40 yr. Many PWH above this age thus have limitations in their activities of daily life. Cardiovascular diseases have become increasingly common in the growing, ageing cohort of PWH. Lifestyle issues such as sexual dysfunction may be exacerbated by the medical issues and psychological problems associated with haemophilia. Hepatitis C virus is a leading problem in PWH. Coinfection with HIV accelerates the progression to end‐stage liver disease. Acute and chronic renal failure is more common in adult PWH than in general population. Other comorbidities are reviewed. The evidence is scarce, so it is imperative to report any experience regarding the diagnosis and treatment of these entities, to improve the quality of life of older PWH.